Real‐world assessment of comprehensive genome profiling impact on clinical outcomes: A single‐institution study in Japan - Kei Kunimasa; Naotoshi Sugimoto; Tomoyuki Yamasaki; Yoji Kukita; Fumie Fujisawa; Tazuko Inoue; Yuko Yamaguchi; Mitsuko Kitasaka; Daisuke Sakai; Keiichiro Honma; Toru Wakamatsu; Sachiko Yamamoto; et al. (Cancer Medicine)
Abstract Introduction Comprehensive genome profiling (CGP) has revolutionized healthcare by offering personalized medicine opportunities. However, its real‐world utility and impact remain incompletely understood. This study examined the extent to which CGP leads to genomically matched therapy and its effectiveness. Methods We analyzed data from advanced solid tumor patients who underwent CGP panel between December 2019 and May 2023 at the Osaka International Cancer Institute. Patient demographics, specimen details, and expert panel assessments were collected. Turnaround time (TAT) and genomically matched therapy outcomes were analyzed. Gene alterations and their co‐occurrence patterns were also assessed. Results Among 1437 patients, 1096 results were available for analysis. The median TAT was 63 [28–182] days. There were 667 (60.9%) cases wherein recommended clinical trials were presented and there were 12 (1.1%) cases that could be enrolled in the trial and 25 (2.3%) cases that could lead to therapies under insurance reimbursement. The median progression free survival of the trial treatment was 1.58 months (95% CI: 0.66–4.37) in clinical trials and 3.66 months (95% CI: 2.14–7.13) in treatment under insurance. Pathologic germline variants were confirmed in 15 patients (1.3%). Co‐alteration of CDKN2A, CDKN2B, and MTAP was significantly observed in overall population. Conclusion The effectiveness of the genomically matched therapy based on the CGP panel was unsatisfactory. Expansion of clinical trials and utilization of remote clinical trials are required to ensure that the results of the CGP panel can be fully returned to patients.